Targeting miRNA with flavonoids: unlocking novel pathways in cardiovascular disease management - Prananda, Arya Tjipta; Halim, Princella; Syahputra, Rony Abdi (Frontiers in Pharmacology, 2025)
Cardiovascular disease (CVD) remains the leading cause of mortality worldwide, with complex pathophysiological mechanisms such as oxidative stress, inflammation, apoptosis, and endothelial dysfunction driving disease progression. MicroRNAs (miRNAs), a class of non-coding RNAs, have emerged as key regulators of gene expression involved in these processes, positioning them as potential biomarkers and therapeutic targets in CVD management. Simultaneously, flavonoids, naturally occurring polyphenolic compounds found in various plant-based foods, have gained attention for their cardioprotective properties, including antioxidant, anti-inflammatory, and anti-apoptotic effects. Recent studies suggest a novel intersection between flavonoids and miRNAs, where flavonoids may modulate the expression of specific miRNAs implicated in CVD pathogenesis. This review explores the potential of flavonoids as miRNA modulators, focusing on their ability to regulate miRNAs associated with cardiac fibrosis, hypertrophy, and vascular inflammation. By bridging the therapeutic potential of flavonoids with miRNA targeting, this review highlights innovative pathways for advancing CVD treatment strategies. Additionally, preclinical and clinical evidence supporting these interactions is discussed, alongside the challenges and opportunities in developing flavonoid-based miRNA therapies. Unlocking this synergy could pave the way for more effective, personalized approaches to CVD management, addressing unmet needs in contemporary cardiovascular care.